(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Mainstream media has, since its inception, proved itself a vehicle for the normalisation of regressive and hegemonic ideologies in society. Media merely assumes a façade of tolerance, inclusion, and innocence to propagate ideals that are inherently queerphobic. Most mainstream media narratives invariably uphold the ‘traditional’ rhetoric of heteronormativity. Homophobic tendencies are not innate in humans; they are shaped by cultural influences, especially in the form of television. Media narratives have induced homophobic tendencies in its consumers through a constant exaltation of ‘hegemonic masculinity. This aggravates the insecurities of the average male heterosexual viewer, pushing them towards aggression or bullying to assert their masculinity. This paper is an exploration of how the adult animated satirical sitcom Family Guy exposes the hypocrisy of media and subsequently subverts the discriminatory ideologies preached within the framework of mainstream representations. Such new wave sitcoms achieve a subversion of deep-rooted gender discrimination through the employment of various language strategies like irony, exaggeration, allusion, polysemy, hyper stereotyping etc. This paper focuses on a detailed study of how the traditional heteronormativity is undermined by discourses on homosexuality. Season Four of Family Guy to substantiate the aforementioned observations.